2009
DOI: 10.1159/000258048
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Uterine Artery Doppler in Patients with Preeclampsia

Abstract: Objectives: To evaluate the predictive capacity of umbilical, cerebral and uterine artery Doppler in women admitted for preeclampsia (PE). Methods: 190 consecutive singleton pregnancies admitted with PE were included. Umbilical, cerebral and uterine artery Dopplers were performed. The association with adverse perinatal outcome was evaluated from 2 × 2 tables and multivariately by logistic regression. Results: A total of 82 (43%) women had an abnormal uterine artery Doppler on admission, being more prevalent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
(28 reference statements)
4
10
1
4
Order By: Relevance
“…Regarding the perinatal prognosis, it is well known that gestational age at onset of PE is highly correlated with outcome, and this has been further confirmed in our study. The usefulness of both mean UtA‐PI and sFlt‐1/PlGF ratio for prognostic assessment in early‐onset PE has been recently highlighted, suggesting that not only gestational age but also placental insufficiency and angiogenic imbalance may have a role in perinatal outcome. We have taken a step forward by showing that the addition of these parameters to gestational age at diagnosis could improve the prognostic accuracy, with sFlt‐1/PlGF ratio showing more promising results than mean UtA‐PI, although our study is probably underpowered and larger studies are needed to establish more firmly the role of the sFlt‐1/PlGF ratio.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the perinatal prognosis, it is well known that gestational age at onset of PE is highly correlated with outcome, and this has been further confirmed in our study. The usefulness of both mean UtA‐PI and sFlt‐1/PlGF ratio for prognostic assessment in early‐onset PE has been recently highlighted, suggesting that not only gestational age but also placental insufficiency and angiogenic imbalance may have a role in perinatal outcome. We have taken a step forward by showing that the addition of these parameters to gestational age at diagnosis could improve the prognostic accuracy, with sFlt‐1/PlGF ratio showing more promising results than mean UtA‐PI, although our study is probably underpowered and larger studies are needed to establish more firmly the role of the sFlt‐1/PlGF ratio.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is of paramount importance to develop new tools to predict which cases are at greatest risk and which are suitable for expectant management in the setting of early‐onset PE. Recent studies have shown that abnormal uterine artery Doppler may be useful in the prediction of adverse fetal outcome, with even higher sensitivity than umbilical artery Doppler, but its specificity is very low. Similarly, it has been reported that the magnitude of the imbalance between anti‐angiogenic (soluble fms‐like tyrosine kinase‐1 (sFlt‐1)) and pro‐angiogenic (placental growth factor (PlGF)) factors correlates well with disease activity, with a cut‐off value of the sFlt‐1/PlGF ratio greater than 655 increasing the risk for imminent delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have suggested that these criteria are inaccurate at predicting maternal and fetal complications. 5, 21, 22 Consistent with this, we found fair predictive value for laboratory values and signs generally considered indicative of severe preeclampsia. In contrast, the sFlt1/PlGF ratio had high predictive value in women at less than 34 weeks gestation and particularly useful among participants who presented atypically.…”
Section: Discussionsupporting
confidence: 85%
“…Both a reduction in placental blood flow and impaired placental structure have been associated with neonatal complications following preeclampsia, such as growth retardation [4][5][6][7]. Specifically, Doppler studies reveal that impaired feto-placental blood flow is mainly evident in women with early-onset preeclampsia (EOPE) [8] rather than late-onset preeclampsia (LOPE) [9]. Moreover, EOPE exhibits placental histological changes related with reduced perfusion [10][11][12][13] as well as the anomalous structure of the peripheral villi and vasculature compared to respective controls identified by stereological analysis following EOPE, but not LOPE [13].…”
Section: Introductionmentioning
confidence: 99%